Exploring the Semantic Meanings of 'نذير' in the Qur'an: Comparative Tafsir Analysis - Burhanudin Al-Ghoni; Eko Sumardianto; Moh Fauzi Rahman Ramdhani; Muhamat mubin (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2023)
This study examines the semantic meanings of the words نذير (nadhir) and ينذر (yunzir) in the Qur'an, which mean